2019
DOI: 10.1055/s-0039-1700867
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Organizational Change to Accommodate an Inpatient Portal

Abstract: Background Patient portals are becoming more commonly used in the hospital inpatient setting. While the potential benefits of inpatient portals are acknowledged, there is a need for research that examines the challenges of portal implementation and the development of best practice approaches for successful implementation. Objective We conducted this study to improve our understanding of the impact of the implementation of an inpatient portal on care team members in the context of a large academic med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…acceptance of an inpatient portal and strategies to enhance the change management process. 5 Two invited papers touched on the adoption of standards, which is a very important topic in clinical informatics. Garcia et al presented "Sync for Genes: Making Clinical Genomics Available for Precision Medicine at the Point-of-Care" where her team describes the use of HL7's emerging FHIR standard in genomics.…”
mentioning
confidence: 99%
“…acceptance of an inpatient portal and strategies to enhance the change management process. 5 Two invited papers touched on the adoption of standards, which is a very important topic in clinical informatics. Garcia et al presented "Sync for Genes: Making Clinical Genomics Available for Precision Medicine at the Point-of-Care" where her team describes the use of HL7's emerging FHIR standard in genomics.…”
mentioning
confidence: 99%
“…1 2 21 Yet getting portals into the hands of hospitalized patients in a reliable manner remains a challenge for many hospitals. 8 11 12 Our findings suggested that the three strategies of establishing provisioning processes, having persistent unit-level champions, and actively promoting the distribution and use of MCB tablets can make a difference in unit provisioning performance.…”
Section: Discussionmentioning
confidence: 80%
“…1,2,21 Yet getting portals into the hands of hospitalized patients in a reliable manner remains a challenge for many hospitals. 8,11,12 Our findings suggested that the three strategies of establishing provisioning processes, having persistent unit-level champions, and actively promoting the distribution and use of MCB tablets can make a difference in unit provisioning performance. Notably, our study results suggest the need to further add to the list of work-related tasks falling to nursing staff who should prioritize, champion, and promote tablet provisioning.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations